Content Analysis of English Learning Material for SMK/MAK XI 2013 Curriculum Published by Bumi Aksara - Anggie Anggie; Suparmi Suparmi; Rahma Dania (Universitas Putra Indonesia YPTK Padang, 2021)
The reseach queations in this study were : Is there any relevant between learning material for SMK/MAK XI 2013 curriculum published by BUMI AKSARA with syllabus? and What is the English textbook learning material for SMK / MAK XI based on the 2013 curriculum published by BUMI AKSARA fulfill criteria based on Nation and Macalister (2010: 160)? The textbooks used in the 2013 curriculum are rarely matched with the syllabus because the teacher thinks that it is not necessary to do so that learning is more relaxed with the method. In the subject of English at SMK N 10 Padang, especially class XI, the textbooks used are published by